Fourth ACP-EEC Convention signed in Lomé on 15 December 1989 : complete text (1990)
Contains general provisions of ACP-EEC cooperation; areas of cooperation as they relate to the environment, agriculture and other industrial sectors. Highlights instruments of cooperation pertaining to inter alia: trade, commodities, and development finance cooperation. Identifies general provisions for Least Developed ACP states, landlocked states and island ACP states. Provides details of the operations of the Institutions. States financial and other protocols.
Keywords: TRADE AGREEMENTS